About a misleading calcified mass of the elbow: Soft tissue osteochondroma: A case report. (June 2022) - Ammar, Ameni; Abcha, Oussama; Berriri, Marouene; Sassi, Samia; Smida, Mahmoud
Abstract: Introduction: Soft tissue osteochondromas are rare lesions, with a misleading radiology, that can present diagnostic dilemma. Case presentation: We report the case of 16-year-old girl who presented an anterior swelling in his left elbow, slightly painful on palpation, with no signs of inflammation. Elbow mobility was normal. Standard radiographs showed a globular calcified mass. CT scan revealed a well-defined lobulated soft tissue mass with extensive flaky calcification. Magnetic resonance imaging (MRI) showed lobulated and intermuscular non-enhancing mass. The lesion had a low heterogeneous signal on T1 images, and a high heterogeneous signal on T2 FAT-SAT images, with low signal areas suggesting calcifications. There was no continuity to the adjacent ulna and radius. The patient first underwent image-guided core needle biopsy and histological examination concluded to chondroma. The tumour was then resected by anterior approach and the final histological diagnosis was osteochondroma of soft tissue. Discussion: A diagnosis of extraskeletal osteochondroma should be considered when an ossified mass is localized in the soft tissue particularly on the elbow. Excision is the treatment of choice when the function is reduced and the nature of the tumour remain uncertain. Conclusion: Orthopedic surgeons should know about elbow localization of osteochondromas to help in accurate diagnosis and management of the tumour, to avoid overtreatment. Highlights: Orthopedic surgeons should know about elbow localization of osteochondromas to help in accurate diagnosis and management of the tumour.